The cellular modifier MOAG‐4/SERF drives amyloid formation through charge complementation. (7th October 2021) - Pras, Anita; Houben, Bert; Aprile, Francesco A; Seinstra, Renée; Gallardo, Rodrigo; Janssen, Leen; Hogewerf, Wytse; Gallrein, Christian; De Vleeschouwer, Matthias; Mata‐Cabana, Alejandro; Koopman, Mandy; Stroo, Esther; et al.
Abstract: While aggregation‐prone proteins are known to accelerate aging and cause age‐related diseases, the cellular mechanisms that drive their cytotoxicity remain unresolved. The orthologous proteins MOAG‐4, SERF1A, and SERF2 have recently been identified as cellular modifiers of such proteotoxicity. Using a peptide array screening approach on human amyloidogenic proteins, we found that SERF2 interacted with protein segments enriched in negatively charged and hydrophobic, aromatic amino acids. The absence of such segments, or the neutralization of the positive charge in SERF2, prevented these interactions and abolished the amyloid‐promoting activity of SERF2. In protein aggregation models in the nematode worm Caenorhabditis elegans, protein aggregation and toxicity were suppressed by mutating the endogenous locus of MOAG‐4 to neutralize charge. Our data indicate that MOAG‐4 and SERF2 drive protein aggregation and toxicity by interactions with negatively charged segments in aggregation‐prone proteins. Such charge interactions might accelerate primary nucleation of amyloid by initiating structural changes and by decreasing colloidal stability. Our study points at charge interactions between cellular modifiers and amyloidogenic proteins as potential targets for interventions to reduce age‐related protein toxicity. Synopsis: The cellular modifier MOAG/SERF2 systematically interacts with negatively charged protein segments through its positively charged N‐terminus. Amyloidogenic proteins are often stabilized by their supercharged segments, and the interaction with and shielding of these charges by MOAG/SERF2 seems to drive amyloidogenic proteins towards aggregation both in vitro and in vivo . The amyloid‐promoting factor SERF2 interacts with negatively charged protein segments, which is enhanced by hydrophobic and aromatic residues Absence of charge interactions abolishes the binding and amyloid‐promoting effect of SERF2 Reducing charge in the evolutionarily conserved N‐terminus of the SERF ortholog MOAG‐4 rescues Caenorhabditis elegans aggregation models, thereby increasing lifespan Abstract : While amyloidogenic proteins are often stabilized by their supercharged segments, the specific interaction with and shielding of these charges by MOAG/SERF2 drives aggregation of amyloidogenic proteins in vitro and in vivo .